2015
DOI: 10.1021/nn505895j
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Activity Expressed by a Library of 2,9-Diazaperopyrenium Dications

Abstract: Polyaromatic compounds are well-known to intercalate DNA. Numerous anticancer chemotherapeutics have been developed upon the basis of this recognition motif. The compounds have been designed such that they interfere with the role of the topoisomerases, which control the topology of DNA during the cell-division cycle. Although many promising chemotherapeutics have been developed upon the basis of polyaromatic DNA intercalating systems, these candidates did not proceed past clinical trials on account of their do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…In this study doxorubicin treatment was only effective in reducing tumor growth in the MDA-MB-231 xenografts, whereas no effect was observed in the FaDu, HT29 –CAIX high and HT29 –CAIX low tumor models. This difference between models is unlikely caused by any intrinsic variation in doxorubicin sensitivity, as no differences were observed in vitro or in previous reports [ 33 ]. The tumor microenvironment might therefore be responsible for this difference in doxorubicin response.…”
Section: Discussionmentioning
confidence: 68%
“…In this study doxorubicin treatment was only effective in reducing tumor growth in the MDA-MB-231 xenografts, whereas no effect was observed in the FaDu, HT29 –CAIX high and HT29 –CAIX low tumor models. This difference between models is unlikely caused by any intrinsic variation in doxorubicin sensitivity, as no differences were observed in vitro or in previous reports [ 33 ]. The tumor microenvironment might therefore be responsible for this difference in doxorubicin response.…”
Section: Discussionmentioning
confidence: 68%
“…According to our previous study, 26 assembly of PTCDI-C6 molecules takes two orientations within one monoclinic crystal cell, as usually observed for other PTCDIs that have tertiary or quaternary carbon atoms directly linked to the imide nitrogen atoms. 5,27 Within the PTCDI-C6 crystal, the stacking molecules twist by an appropriate angle to minimize the steric hindrance of cyclohexyl groups. But with the inserting of coronene molecules, the distance between the two PTCDI-C6 molecules was almost doubled, thus diminishing the steric hindrance of side groups.…”
mentioning
confidence: 99%
“…Golunski[69] and co-workers hypothesized that doxorubicin toxicity could be reduced without loss of efficacy by disrupting its π-π self-recognition with pentoxifylline (S2 Fig)–an aromatic molecule known to breakup π-π -stacking. Hartlieb[70] and colleagues attacked this problem differently—they showed that disruption of the π-stacking of 2,9-diazaperopyrenium by adding a functional group that causes a steric clash with the neighboring molecule, results in increased anti-cancer potency (S2 Fig). These investigators solved the crystal structures of the homo-aggregates and demonstrated that biological activity increased as stacking decreased.…”
Section: Discussionmentioning
confidence: 99%